THE RELATIONSHIP BETWEEN MOTIVATION AND SATISFACTION AMONG E-SPORTS ATHLETES IN THE PUBLIC UNIVERSITIES - Md Puad, Muhammad Adli Amirul; Albalushi, Mohammed Ali (Journal of Human Capital Development (JHCD), 2025)
ABSTRACT Studies on e-sports (e-sports) involvement factors are still lacking in the Malaysian context. Accordingly, the objective of this study was to examine the relationship between motivation and satisfaction among e-sports athletes at Melaka Public universities. The study respondents consisted of 150 e-sports athletes, who participated in e-sports tournaments, from public universities in Melaka. Data were distributed to respondents who were involved in e-sports held from 2020 to 2022. Descriptive analysis and Pearson correlation were used to study the relationship between motivation and satisfaction among e-sports athletes at public universities in Malacca. Based on the findings, the descriptive analysis of Entertainment Motivation (MH) among E-sports Athletes scored the highest mean value with a mean score of 4.0. Meanwhile, the descriptive analysis of Diversion Motivation (ML) among E-sports Athletes showed medium and low values in contrast to other factors, the mean score =3. As a result of the research findings, there is a motivational influence of competition, diversion, entertainment, fantasy, social, and complements on satisfaction among e-sports athletes of public universities in Melaka. There are many advantages that can be seen in the development of this electronic sport such as in terms of careers and government involvement regarding Industrial Revolution 4.0. Keywords: motivation, electronic sport, satisfaction, public universities